Synthesis of Molecularly Imprinting Polymers for the Removal of Xylenol Orange from Water - Showkat, Ahmad Bhawani; Nur Anati Bazilah, Daud; Salma, Bakhtiar; Rachel Marcela, Roland; Mohamad Nasir, Mohamad Ibrahim (2020)
The molecularly imprinted polymers (MIPs) were prepared by using the non-covalent approach. In the polymerization process, xylenol orange was used as a template (T), acrylic acid as a functional monomer (M), divinylbenzene as a cross-linker (CL) and 2,2’-azobisisobutyronitrile (AIBN) as an initiator and microemulsion as a solvent. The synthesized polymers were characterized by using FTIR and SEM micrograph. The batch binding analysis was used to evaluate the rebinding efficiency of imprinted polymers. The highest rebinding efficiency was obtained from the MIP-R2 (0.1:0.6:2, T:M:CL). The selected MIP-R2 was used for the removal of xylenol orange from the water sample and have shown removal efficiency of about 80%.